ISSUES OF RELAPSES IN ADULT PATIENTS WITH EPILEPSY - V. A. Karlov; E. M. Rokotyanskaya; G. A. Kovalenko (Эпилепсия и пароксизмальные состояния)
The given work has been undertaken for an estimation of major factors of failure of remission of an epilepsy, and also correlation revealing between duration of disease and risk of relapse. We had been surveyed and analysed 104 patients with an epilepsy, without expressed mental retardation, observed in medical center «Nevromed». From them to the basic group - (relapse presence) has been carried 76 persons, to control group - (without relapse) - 28 patients. The importance of two major factors has been revealed: forms of an epilepsy and current type. The probability of relapse, according to the received results, remains throughout all duration of disease.